The impact of creative behaviors of employees on the performance of government institutions in Karak - Al-Khatatneh, Maysoon Karim (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to identify the level of creative behavior, and to identify the strengths and weaknesses of the variables of creative behavior (brainstorming, ability to change, problem solving) in government institutions in Jordan. The study aimed to identify the level of institutional performance, and analyze the impact of creative behaviors of employees on the performance of government institutions in Jordan. The study adopted descriptive & analytical methodology based on a questionnaire applied to a sample of 50 employees in government institutions. The study found that there is a statistically significant relationship between the creative behaviors of employees and performance in government institutions in Jordan, and in the light of the findings, the study reached the recommends to increase attention to the creative behavior of employees in government institutions.